Some Metaphors of COVID-19 Pandemic - Fossile, Dieysa Kanyela (Lingüística y Literatura, 2021)
In this article, nominal metaphors related to COVID-19 are analyzed, referred to as covitáforas-19 (COVID-19 metaphors). From a bibliographical and qualitative approach, the objective of the study was to encourage dialogue between interaction theory and the metaphorical descriptions of COVID-19. It was found that interlocutors and readers are able to achieve plausible interpretations of COVID-19 metaphors through the identification, selection, and interaction between the properties relevant to both the topic and the vehicle. The studied metaphors were found to provide coherent information on COVID-19 and to be able to inspire a variety of sensations in both readers and interlocutors.